Betriebsratsgründungen als kollektive Deutungskämpfe um Mitbestimmung - Artus, Ingrid; Röhrer, Stefan (Industrielle Beziehungen - Zeitschrift für Arbeit, Organisation und Management, 2019)
The present text seeks to dismantle the disciplinary barrier between movement research and theory of industrial relations by using elements of mobilization theory for analysing works council foundations. Initiatives for implementing a works council are interpreted as mobilization incidents in terms of political interest. It is crucial for the development whether core groups on the shop floor level succeed in re-framing the hegemonic political culture of relationships between management and labour. Analysing two examples of work council implementation – a successful case and a failed one – helps to identify relevant factors influencing the success of works council initiatives.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Co-determination; Collective mobilization processes; Framing; Mobilization theory; Movement research; Works council; Works council foundations